The Impact of Zakat Management Accounting Information System Quality on Muzaki Satisfaction in Indonesia - Nunung Nurhayati; Dewi Sartika; Ririn Sk; Ayunazwa; M Rakan; Ridwan (UPT Publikasi Ilmiah UNISBA, 2024)
The potential for zakat in Indonesia is very large, but in reality only 5% of zakat fund collection is obtained from this potential. Many factors influence the low acceptance of zakat funds, including the quality of the zakat management accounting information system which has an impact on decreasing the satisfaction of muzaki. The purpose of the study was to measure how much influence the quality of the management accounting information system has on the satisfaction of system users. While the research method used is explanatory research. With a sample of 100 muzaki, the data collection technique used a questionnaire, the research instrument used a validity and reliability test, the data analysis technique used SEM-PLS with an inner model and outer model. The results of this study prove that the quality of the zakat management accounting information system has a positive and significant effect on muzaki satisfaction. The results of this study provide a real contribution to zakat fund managers to pay attention to the quality of the management accounting information system that can provide speed and ease of information for muzaki, so that muzaki feel satisfied to deposit zakat funds in the amil institution which has an impact on the level of zakat fund collection increasing.